Divalent heavy metal cations block the TRPV1 Ca2+ channel - Winter, Zoltan; et al. (Biological trace element research, 2013)
Transient receptor potential vanilloid 1 (TRPV1) is a non-selective cation channel involved in pain sensation and in a wide range of non-pain-related physiological and pathological conditions. The aim of the present study was to explore the effects of selected heavy metal cations on the function of TRPV1. The cations ranked in the following sequence of pore-blocking activity: Co2+ [half-maximal inhibitory concentration (IC50) = 13 μM] > Cd2+ (IC50 = 38 μM) > Ni2+ (IC50 = 62 μM) > Cu2+ (IC50 = 200 μM). Zn2+ proved to be a weak (IC50 = 27 μM) and only partial inhibitor of the channel function, whereas Mg2+, Mn2+ and La3+ did not exhibit any substantial effect. Co2+, the most potent channel blocker, was able not only to compete with Ca2+ but also to pass with it through the open channel of TRPV1. In response to heat activation or vanilloid treatment, Co2+ accumulation was verified in TRPV1-transfected cell lines and in the TRPV1+ dorsal root ganglion neurons. The inhibitory effect was also demonstrated in vivo. Co2+ applied together with vanilloid agonists attenuated the nocifensive eye wipe response in mice. Different rat TRPV1 pore point mutants (Y627W, N628W, D646N and E651W) were created that can validate the binding site of previously used channel blockers in agonist-evoked 45Ca2+ influx assays in cells expressing TRPV1. The IC50 of Co2+ on these point mutants were determined to be reasonably comparable to those on the wild type, which suggests that divalent cations passing through the TRPV1 channel use the same negatively charged amino acids as Ca2+.<br
Keywords: TRPV1; Calciumchannel; Pain; Somatosensory system; Cobalt; Heavy metals